Leaving the Labor Market Early in Sweden – Learning from International Experience - Mats Bengtsson; Stefanie König; Simon Schönbeck; Eskil Wadensjö (Institute of Labor Economics (IZA), 2022)
It is a challenge for politics that an aging population leads to demands that the retirement age is increasing while not everyone is able to work to such a higher age. Sweden, like other countries, has several options for early exit from the labour market. However, the regulations have become more restrictive in the last decade and early retirement usually leads to a lower pension. In this article, we map options for early retirement in other countries. We have found five main types that all have both advantages and disadvantages. There are also problems with integrating them into the Swedish pension system.
Keywords: H55; J11; J14; J21; J26; 330; retirement; employment; pensions; early exit